2010
DOI: 10.1093/toxsci/kfq269
|View full text |Cite
|
Sign up to set email alerts
|

Interference with Bile Salt Export Pump Function Is a Susceptibility Factor for Human Liver Injury in Drug Development

Abstract: The bile salt export pump (BSEP) is an efflux transporter, driving the elimination of endobiotic and xenobiotic substrates from hepatocytes into the bile. More specifically, it is responsible for the elimination of monovalent, conjugated bile salts, with little or no assistance from other apical transporters. Disruption of BSEP activity through genetic disorders is known to manifest in clinical liver injury such as progressive familial intrahepatic cholestasis type 2. Drug-induced disruption of BSEP is hypothe… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

10
335
2
2

Year Published

2011
2011
2017
2017

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 304 publications
(352 citation statements)
references
References 73 publications
10
335
2
2
Order By: Relevance
“…Those were therefore not considered as inhibitors. Morgan et al 16 measured the BSEP inhibition activity of 217 compounds to relate them with liver injuries. Compounds with IC 50 below 25 µM were taken as inhibitors, while compounds with IC 50 over 135 µM were taken as non-inhibitors.…”
Section: External Validationmentioning
confidence: 99%
See 2 more Smart Citations
“…Those were therefore not considered as inhibitors. Morgan et al 16 measured the BSEP inhibition activity of 217 compounds to relate them with liver injuries. Compounds with IC 50 below 25 µM were taken as inhibitors, while compounds with IC 50 over 135 µM were taken as non-inhibitors.…”
Section: External Validationmentioning
confidence: 99%
“…Compounds with IC 50 below 25 µM were taken as inhibitors, while compounds with IC 50 over 135 µM were taken as non-inhibitors. The 25 µM threshold was chosen because, among the compounds that were present both in the training set and in 16 , the equivalent IC 50 in the training set was usually below 10 µM. The chemical structures were retrieved by name from Pubchem Compound (http://www.ncbi.nlm.nih.gov/pccompound).…”
Section: External Validationmentioning
confidence: 99%
See 1 more Smart Citation
“…Impaired bile acid export may lead to increased concentrations of liver bile acids, causing hepatocellular apoptosis and/or necrosis. Thus, drugs with the potential to inhibit these transporters can disturb the disposition of both co-administered drugs and bile acid, contributing to the development of cholestatic drug-induced liver injury (DILI) [42,43]. In vitro studies with isolated membrane vesicles have demonstrated an association between DILI and the inhibitory effects of drugs on bile acid efflux transporters [43][44][45].…”
Section: Pbpk For the Prediction Of Transporter-mediated Drug Inducedmentioning
confidence: 99%
“…However, BSEP is inhibited by a great variety of drugs and, thus, plays a crucial role in the pathogenesis of drug induced cholestatic liver disease [18,[73][74][75]. MRP3 mediates biliary phospholipid secretion [76], ABCG5/ABCG8 facilitates canalicular cholesterol release [77] and the p-type ATPase ATP8B1 is essential for canalicular bile formation and probably acts as an animophospholipid flipase [78].…”
Section: Drug Transporters In the Livermentioning
confidence: 99%